Analysis of Secreted Proteins and Potential Virulence via the ICEs-Mediated Pathway of the Foodborne Pathogen Vibrio parahaemolyticus - He, Yu; Wang, Shuai; Wang, Kaiwen; Zhou, Jinwei; Han, Zhi; Sun, Fengjiao (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus uses bacterial secretion systems and integrative and conjugative elements (ICEs) to induce various diseases and to adapt to harsh environments, respectively. Information pertaining to the identity of secreted proteins and functional characterization of ICEs has been previously reported, but the relationship between these elements remains unclear. Herein we investigated secreted proteins of Vibrio parahaemolyticus strains JHY20 and JHY20△ICE using two-dimensional gel electrophoresis and LC–MS/MS, which led to the identification of an ICE-associated secreted protein—dihydrolipoamide dehydrogenase. Considering the data related to its physical and biochemical characterization, we predicted that dihydrolipoamide dehydrogenase is a novel immunogenic protein and associated with virulence in JHY20. Our findings indicate a potential relationship between ICE-associated transport and secreted proteins and shed light on the function of such transport mechanisms. We believe that our data should enhance our understanding of mobile genetic elements.